Biodiversity and Structure of Rotifera Communities in the Great Garraf Drain Channel, Southern Iraq - Al-Safi, Duaa R. M.; Nashaat, Muhanned R.; AL-Sariy, Jameel S. (Iraqi Journal of Science, 2022)
Three sites, selected on the Great Garraf Drain Channel (GGDC) demonstrated the first ever study dealing with rotifers biodiversity features from August 2019 till July 2020. Seventy-two taxonomic units were identified. The high densities of rotifera ranged from 733.32 - 32300 Ind./m3. Brachionus urceolaris, Keratella quadrata (long spin), Keratella quadrata (short spin) and Syncheta obloga were the most common relative abundance recorded in the index. In contrast the results of the constant index showed that there were nine constant taxonomic units. The species richness index was recorded from 1.489- 6.900. Jaccard presence similarity index revealed a strong link between stations 2 and 3 with a value of 83.30%. Hereinafter Shannon-Weiner diversity index recorded values ranging from 0.821-2.901 bit/Ind. The species uniformity index ranged from 0.296- 0.925. Nevertheless, the values of this index indicated no environmental stress on rotifera assemblage in the river environment. Also, it was concluded that GGDC was considered generally ranging from moderately polluted in some sites to highly polluted water in other locations during the study period.